Challenges to patients’ rights during the COVID-19 pandemic: survey of public perceptions in North Macedonia - Katerina Kuzmanova; Aleksandar Dimkovski; Evgenija Mihajloska; Aleksandra Grozdanova; Katerina Anchevska Netkovska (Makedonsko Farmacevtski Bilten)
The COVID-19 pandemic exposed significant challenges in upholding patient rights within Macedonian healthcare system. An online survey of 145 citizens assessed their perceptions regarding access to healthcare, informed consent, autonomy, and privacy during the pandemic. Results showed that 65.5% of respondents had access to essential services and 95.2% did not experience discrimination. Although 72.4% felt adequately informed about their care throughout all phases, just under half (47.6%) were aware of their healthcare and insurance rights and the procedures to secure them. Two-thirds (67.6%) reported that their autonomy was respected despite restrictive measures, and over 70% believed their privacy was maintained. These findings highlight both strengths and areas for improvement, emphasizing the need for enhanced and detailed delivery of information by healthcare professionals. Addressing these issues is crucial for refining healthcare policies and practices, ensuring equitable and effective care, and better protecting patient rights during future public health emergencies in North Macedonia.